Biomaterials and Regenerative Agriculture: A Methodological Framework to Enable Circular Transitions - Garmulewicz, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Biomaterials, used here to signify 100% biobased and biodegradable materials, can offer a promising solution for transitioning away from fossil-based resources, addressing the climate crisis, and combating plastic pollution. To ensure their environmental benefits, biomaterials must derive from regenerative, non-polluting feedstocks that do not compete with food or feed production. From this perspective, agricultural residues and by-products present a favorable feedstock option for biomaterials production. Although this is an improvement over sourcing them from primary crops, the sustainability of underlying agricultural systems must be considered. Furthermore, the nutrient value of biomaterials for specific soil ecosystems is often overlooked despite their compostability. In this research, we investigate the linkages between biomaterials development and regenerative agriculture, a set of farming practices that can effectively sustain the growing human population while enhancing, rather than degrading, ecosystem health. We explore interdependencies between biomaterials’ production and regenerative agriculture for biomass sourcing and nutrient return and suggest a methodological framework to identify mutual benefits. The extent to which regenerative farms can provide biomaterial feedstocks without compromising crop cultivation and ecosystem health is analyzed together with the potential of biomaterials to deliver beneficial nutrients and services to regenerative systems. Applying this framework to the Great Lakes Region, Michigan, USA, an agricultural hub facing environmental degradation and plastic pollution, reveals synergistic linkages that unlock novel circular economy opportunities, including local production of renewable biomaterials for various applications, enhancing food security and bolstering socio-ecological systems. © 2023 by the authors.